Riview Artikel Tumbuhan Kitolod dalam Tumbuhan Fitokimia dan Farmakologi - Zinda Rizkia Aprilia; Ardi Mustakim (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Isotoma Longiflora Presi known as kitolod belongs to the Campanulaceae family. This plant is used as traditional medicine, and now continues to be in the process of moving towards conventional herbal medicine. Kitolod plants grow scattered on several islands in Indonesia, especially in the lowlands. This review article discusses the scientific journal of the kitolod plant which focuses on chemical compounds and also their pharmacological activities. All information exposure obtained from scientific literature such as scientific journals, the official website of the Minister of Health, books and also electronic books. Based on the results of a literature survey, Kitolod Plant (Isotoma Longiflora Presi). used in traditional medicine, used as anticancer, anti-inflammatory, anti-fungal, anti-bacterial, anti-oxidant, and is also able to help treat glaucoma and hyperlepidemia. Phytochemical compounds contained in this plant are alkaloids, flavonoids, tannins, saponins, terpenoids and steroids. This finding was obtained from both in vivo and in vitro testing and analysis of Isotoma Longiflora Presi.